Prospects of betulin application in broiler farming - M. V. Novikova; I. A. Lebedeva; L. I. Drozdova; A. V. Byuler (Ветеринария сегодня)
It is an urgent task today to seek and implement nature-like technologies in broiler production and obtain biologically complete and safe poultry products, thus refusing from antibiotic use in feed. Feed additives based on natural components can be an effective tool for implementation of preventive and therapeutic veterinary measures. The paper presents research study results of application of betulin-based phytobiotics in broiler farming. The tests were carried out on Ross-308 cross-breed broiler chickens within the production cycle at one of the poultry farms of the Sverdlovsk Oblast. Birds of the experimental group received compound feed supplemented with dry betulin at 2.5 mg/kg of live weight from day 21 to day 35 of growing. The introduction of betulin-based feed additive into the diet contributed to increase in live weight gain and 7.6% pectoralis muscle output as compared with the control group. It was established that the phytobiotic consumption resulted in reduced deposition of subcutaneous and abdominal fat, higher biological value of meat by increasing the ash content, improved technological properties of meat due to increasing water-holding capacity of muscle fiber and intensity of formation and maturation of muscle fiber. Histological studies of pancreatic tissue samples from broiler chickens showed increase in the mass of islets of Langerhans and insulin-producing cell complexes. The pancreas was activated due to effects of the betulin-based feed additive. The results obtained indicate that the use of betulin in broiler production is a promising trend.